Polypyrrole/tannin biobased nanocomposite with enhanced electrochemical and physical properties - Abdi, Mahnaz M.; Mohd Azli, Nur Farhana Waheeda; Lim, Hong Ngee; Md. Tahir, Paridah; Karimi, Gholamreza; Hoong, Yeoh Beng; Khorram, Mohammad (Royal Society of Chemistry, 2018)
In this research, tannin (TA) extracted from Acacia mangium and a cationic surfactant, cetyltrimethylammonium bromide (CTAB), were used to modify and enhance the physical and electrochemical properties of a polypyrrole (PPy) composite. Brunauer–Emmett–Teller (BET) analysis presented a higher degree of surface area and porosity for the PPy/TA/CTAB nanocomposite. A highly porous and rod like structure with a lumpy surface was observed for PPy/TA prepared in the presence of CTAB by Field Emission Scanning Electron Microscopy (FESEM) and Transmission Electron Microscopy (TEM). Cyclic voltammograms of the modified SPE electrode using PPy/TA/CTAB displayed an enhanced current response compared to the electrode modified with only PPy or PPy/TA. Electrochemical Impedance Spectroscopy (EIS) exhibited a lower value of charge transfer resistance (Rct) and higher electron transfer for the modified electrode, making the nanocomposite a promising candidate for biosensor application.